Analisis Kandungan Mangan (Mn) dan Tembaga (Cu) dalam Bijih Mangan di Daerah Taming Tonga Kecamatan Ranah Batahan Kabupaten Pasaman Barat Secara Spektrofotometri Serapan Atom - Widya Pasema; Amrin .; Edi Nasra (Jurnal Periodic Jurusan Kimia UNP, 2012)
A research on the analysis of Manganese and copper content in the manganese ore in the area Taming Tonga artifacts using atomic absorption spectrophotometry had been done. This study aims to determine the content of manganese (Mn) and copper (Cu) with variation of solvent, particle size variations, and solvent volume variations in atomic absorption spectrophotometry. This study uses a wet method of destruction, the destruction process is done with some variation of the solvent variation: concentrated HCl, concentrated HNO3 and HCl-HNO3 concentrated (3:1), variations in particle size is ≤ 63 μm,> 63 - ≤ 75 μm, and> 75 - ≤ 90 μm and variations in volume 20 mL, 25 mL, 30 mL, 35 mL, 40 mL. The results of this study showed the highest manganese content in the samples obtained by using Aquaregia 30 mL that is 57 % with particle size ≤ 63 μm while the highest levels of copper in samples obtained by using a solvent which is 1,89 % HCl 25 mL with particle size ≤ 63 μm best.